The cGAS-STING pathway and its functions in immune defense and inflammatory regulation in teleost fish - Qiyang Wang; Xiuying Cui; Mitong Guo; Yichen Liu; Feng Gao; Xianghui Kong (Fish & Shellfish Immunology, 2026)

Tyrosine hydroxylase as a therapeutic target: insights from adrenergic nerve and TNBC cell interactions - Yichen Luo; Yanhong Han; Huilong Nie; Minghao Feng; Cuiting Wei; Xiuling Ma; Kefeng Li; Zhuangzhuang Zhang; Guangxue Wang; Wenjun Pan; Xueyang Li; Liutong Yi; et al. (Journal of Molecular Medicine, 2026)

TRPS1 inhibits cervical cancer progression by suppressing ORC6-mediated tumor stemness - Juan He; Ruyu Yan; Yitong Du; Huiling Yang; Yichen Feng; Min Tian; Zejun Wu; Lei Li; Lan Xiang; Duoxiang Sun; Xianghua Li; Kecheng Zhou; et al. (Tissue and Cell, 2026)

Orders-of-magnitude reactivity enhancement in persulfate activation by curvature-dependent oxygenated carbon nanotubes - Xin Yang; Zhongyuan Guo; Pufan Wang; Justin Prabowo; Yangyang Wang; Jiaxiang Chen; Jiacheng Wu; Xinyi Huang; Yichen Feng; Chengli Rong; Fangzhou Liu; Hao Li; et al. (Chemical Engineering Journal, 2026)

Hepatic cytochrome P450 induction following Kashin-Beck disease-related selenium deficiency and T-2 toxin exposure in mice - Tong Zhao; Yichen Zhao; Tingting Mao; Weixuan Da; Lina Qin; Li Liu; Huan Liu; Bolun Cheng; Yan Wen; Feng Zhang; Yumeng Jia (Archives of Toxicology, 2026)

Multimodal flow matching for large-scale human mobility flow generation using satellite imagery and social sensing data - Yichen Xu; Yusen Hu; Song Gao; Qiang Zhu; Feng Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Peripheral CD4 T-Cell State Remodeling in Migraine Revealed by Single-Cell RNA Sequencing - Quan Feng; Yichen Li; Na Li; Weisheng Zhan; Ge Tan (Journal of Molecular Neuroscience, 2026)

Collaborative optimization pathway of provincial power generation structure in China - Yan Nie; Guoxing Zhang; Yutao Wang; Bin Su; Yichen Feng; Lean Yu (Mitigation and Adaptation Strategies for Global Change, 2026)

Rigid-flexible coupling errors calibration based on machine learning for robotic harvesting arm in orchard - Yichen Qiao; Qingchun Feng; Liping Chen; Congju Shen; Wenqiao Lu; Yajun Li; Yuhang Ma; Hongwen Li (Computers and Electronics in Agriculture, 2026)

Advanced Bond-Based Peridynamic Modeling of Rock-Like Material Failure: Insights into Crack Propagation and Mechanical Behavior - Pengfei Ma; Yichen Zhang; Jun Chen; Tianjun Feng; Chenglu Gao; Lichao Nie (Rock Mechanics and Rock Engineering, 2026)

Soaking reshapes the structure, function, and co-occurrence patterns of barley surface bacterial communities - Ziyan Zhao; Xiding Wang; Jia Feng; Shulian Xie; Yichen Qiao; Tong Chen; Guofang Xing; Yang Liu (World Journal of Microbiology and Biotechnology, 2026)

Reducing agent-enhanced printed circuit board sludge-based Fenton process for the efficient treatment of coking wastewater: Performance, optimization and mechanism - Fengcheng Jiang; Guangyi Zhu; Chuanbing Zhang; Baoguo Yang; Yichen Zhang; Xiao Xu; Xixi Feng; Fayang Guo; Shuguang Zhao; Huifang Wang; Yahui Xu; Mingshi Wang (Journal of Environmental Sciences, 2026)

Bisphenol A disrupts cartilage homeostasis through CYP2C19 - Yichen Bai; Kai Feng; Tengyao Niu; Xu Bai; Zhirong Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Quantitative evaluation of the evaporator configuration’s implications on the performance enhancement in CO2 thermal management system for electric vehicle - Jianmin Fang; Yichen Zhang; Fan Jia; Xiang Yin; Bin Chen; Feng Cao; Xiaolin Wang (International Journal of Refrigeration, 2026)

Polystyrene microplastics alter the toxicity of 6PPD to zebrafish (Danio rerio) larvae - Yuexing Zhao; Weitao Liu; Jianfeng Feng; Ning Gao; Jinzheng Liu; Ruiying Shi; Aurang Zeb; Jianling Wang; Qi Wang; Chuan Yin; Xinwei Shi; Xiang Li; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

ATP synthase subunit γ mediates Cry1Ac binding and toxicity in Grapholita molesta - Jiayang Feng; Dandan Pan; Yichen Wang; Xiaoyan Zhang; Xiaofang Sha; Yanshen Fu; Jiacheng Ye; Donghan Wang; Xiangqun Yuan; Yiping Li (Pesticide Biochemistry and Physiology, 2025)

Comprehensive analysis of prevailing weather patterns and high-impact typhoon tracks to reveal where and how tropical cyclone affects regional ozone pollution in the Yangtze River Delta region, China - Mengzhu Xi; Yi Luo; Yichen Li; Danyang Ma; Lingyun Feng; Shuxian Zhang; Shitong Chen; Min Xie (Atmospheric Environment, 2025)

Determination of 99Tc in TBP phase in spent nuclear fuel reprocessing with plastic scintillation resin - Man Wang; Tianyi Jia; Yiman Lu; Chenyang Peng; Hao Wang; Yichen Hu; Feng Zhang; Shan Xing; Keliang Shi; Weichao Zhang; Xiaolin Hou (Analytica Chimica Acta, 2025)

Application of cysteine with Cu2+ to strengthen Fenton-based treatment of coking wastewater used ferric sludge as a source of iron catalyst: Cl- removal and Fe3+/Fe2+ cycling - Fengcheng Jiang; Yichen Zhang; Xiao Xu; Yuxiang Mao; Mingshi Wang; Baoguo Yang; Chuanbing Zhang; Xixi Feng; Hongqi Meng; Fayang Guo; Qiao Han; Shengguang Zhang (Journal of Environmental Chemical Engineering, 2025)

Enhanced conductivity and energy storing performances of 3D bimetallic conductive metal-organic frameworks based on linear π-conjugated thiazole for supercapacitors - Chungui Wang; Yichen He; Junping Xie; Siyi Wang; Yingjun Chen; Xu Yang; Yong Pei; Naien Shi; Mong-Feng Chiou; Linghai Xie; Xiaomiao Feng; Min Han (Chemical Engineering Journal, 2025)

Tribopotential mediated ferroelectric polarization for versatile reconfigurable p–n junction - Keteng Zhang; Jinran Yu; Yichen Wei; Liuqi Cheng; Zhenyu Feng; Jie Gong; Zhong Lin Wang; Qijun Sun (Chemical Engineering Journal, 2025)

Enhancement of cellulosome expression by deletion of an HtrA protein in Clostridium thermocellum - Yichen Qiao; Chao Chen; Yingang Feng (Bioresource Technology, 2025)

Evolution of subcritical and transcritical cycles and the quantitative influence of heat exchangers configuration on CO2 automotive heat pumps - Yichen Zhang; Jianmin Fang; Xiang Yin; Bin Chen; Feng Cao; Xiaolin Wang (International Journal of Refrigeration, 2025)

The Effect of the Belt and Road Initiative (BRI) on Non-CO2 Agricultural Greenhouse Gas Emission Trends in Southeast Asian Countries - Minpeng Chen; Siqi Li; Xun Su; Yichen Feng; Yichun Peng (Resources, Conservation and Recycling, 2025)

Assessment of ecological risks and spatiotemporal monitoring of heavy metal contamination in cultivated soils of the Liaohe River Basin, Jilin Province, China - Yanan Chen; Jie Wang; Dianqi Pan; Yichen Zhang; Jiquan Zhang; Feng Zhang; Zengkang Lu (Science of The Total Environment, 2025)

Use of the diffusive gradients in thin-films (DGT) technique for smart rapid biomonitoring of trace metals in aquaculture systems - Runmei Wang; Jian Lu; Jun Wu; Yichen Lin; Feng Li; Cui Zhang; Jianhua Wang; Yingmin Zhou; Xiupeng Yue (Marine Environmental Research, 2025)

Independent Tri-Spectral Integration for Intelligent Ship Monitoring in Ports: Bridging Optical, Infrared, and Satellite Insights - Yichen Feng; Hui Yin; Hao Zhang; Langtao Wu; Haihui Dong; Jiawen Li (Journal of Marine Science and Engineering, 2024)
Image-based ship monitoring technology has extensive applications, and is widely used in various aspects of port management, including illegal activity surveillance, vessel identification at entry and exit points, channel and berth management, unmanned vessel control, and incident warning and emergency response. However, most current ship identification technologies rely on a single information source, reducing detection accuracy in the complex and variable marine environment. To address this issue, this paper proposes a knowledge transfer-based ship identification system integrating three modules. The system enables synchronized monitoring of visible light coastal images, satellite cloud images, and infrared spectrum images, thereby mitigating problems such as low detection accuracy and poor adaptability of image recognition. Additionally, extensive supplementary experiments were conducted to evaluate the effectiveness of the preprocessing and data augmentation modules as well as the transfer learning module. The study also discusses the limitations of current deep learning-based ship monitoring models, particularly their poor adaptability to image recognition and inability to achieve all-weather, round-the-clock monitoring. Experimental results based on three ship monitoring datasets demonstrate that the proposed system, by integrating three distinct detection conditions, outperforms other models with an F1-score of 98.74%, approximately 10% higher than most existing ship detection systems.

Metal-support interaction manipulate the sulfidation and morphology of MoS2 slabs with dominant double-layer structure via surfactant assistance for CO hydrogenation to higher alcohols - Yihua Cao; Xueli Yin; Yonghao Gan; Run Cai; Qi Wang; Bo Feng; Yindan Wu; Likun Wen; Yichen Song; Xiaoping Dai (Fuel, 2024)

Machine vision-assisted genomic prediction and genome-wide association of spleen-related traits in large yellow croaker infected with visceral white-nodules disease - Yulin Bai; Miaosheng Feng; Ji Zhao; Jiaying Wang; Qiaozhen Ke; Zhou Jiang; Pengxin Jiang; Sijing Chen; Longyu Chen; Wei Liu; Tingsen Jiang; Yichen Li; et al. (Fish & Shellfish Immunology, 2024)

Topological surface states in quasi-two-dimensional magnetic kagome metal EuTi3Bi4 - Zhicheng Jiang; Tongrui Li; Jian Yuan; Zhengtai Liu; Zhipeng Cao; Soohyun Cho; Mingfang Shu; Yichen Yang; Zhikai Li; Jiayu Liu; Jianyang Ding; Zhonghao Liu; et al. (Science Bulletin, 2024)

Effects of Vascular Risk Factors on the White Matter Network Architecture of the Brain - Hao-Jie Chen; Weijie Huang; Xinyi Dong; Guozheng Feng; Zhenzhao Liu; Yichen Wang; Junjie Peng; Zhengjia Dai; Ni Shu (Neuroscience Bulletin, 2024)

Enhancement of Mn2+, Fe2+ and NH4+-N removal by biochar synergistic strains combined with activated sludge in real wastewater treatment - Shuman Deng; Qiang An; Jiali Song; Yichen Yang; Zhiruo Huang; Shuyun Feng; Chuanzhu Tang; Bin Zhao (Chemosphere, 2024)

Bone tissue engineering based on sustained release of MiR29c-modified framework nucleic acids from an injectable hydrogel - Jiafei Sun; Yang Gao; Yangxue Yao; Yong Li; Maogeng Feng; Long Bai; Xingyu Chen; Yichen Ge; Yunfeng Lin; Xiaoxiao Cai (Chemical Engineering Journal, 2024)

GhHB14_D10 and GhREV_D5, two HD-ZIP III transcription factors, play a regulatory role in cotton fiber secondary cell wall biosynthesis - Shuaijie Li; Mengli Yu; Ghulam Qanmber; Mengru Feng; Ghulam Hussain; Yichen Wang; Zuoren Yang; Jie Zhang (Plant Cell Reports, 2024)

The social network perspective on power system co-evolution: responses to “double carbon target” realization in China - Xiulin Gao; Guoxing Zhang; Yan Nie; Xi Xi; Yichen Feng (Environmental Science and Pollution Research, 2024)

Exploring building component thermal storage performance for optimizing indoor thermal environment – A case study in Beijing - Yichen Han; Zhengnan Zhou; Wenwen Li; Jiajia Feng; Chaohong Wang (Energy and Buildings, 2024)

An integrative protocol for one-step PCR amplicon library construction and accurate demultiplexing of pooled sequencing data - Jiahao Ni; Jiao Pan; Yaohai Wang; Tianhao Chen; Xinshi Feng; Yichen Li; Tongtong Lin; Michael Lynch; Hongan Long; Weiyi Li (Marine Life Science & Technology, 2023)

Relationships between urban expansion and socioenvironmental indicators across multiple scales of watersheds: a case study among watersheds running through China - Xinyu Zhou; Wenshuo Peng; Yichen Guo; Peiyuan Chen; Qiang Ren; Xingyun Feng; Pengxin Wu; Qingxu Huang (Environmental Science and Pollution Research, 2023)

Assessment of contaminants associated with gold-standard ancient DNA protocols - Bo Miao; Yalin Liu; Ruowei Yang; Xiaotian Feng; Feng Liu; Peng Cao; Qingyan Dai; Wanjing Ping; Yichen Liu; Qiaomei Fu (Science Bulletin, 2023)

Continuous flow modulates zein nanoprecipitation solvent environment to obtain colloidal particles with high curcumin loading - Haocheng Guo; Yiming Feng; Yong Deng; Tianyi Yan; Zimo Liang; Yichen Zhou; Wei Zhang; Enbo Xu; Donghong Liu; Wenjun Wang (Food Hydrocolloids, 2023)

Functional genes and thermophilic microorganisms responsible for arsenite oxidation from the shallow sediment of an untraversed hot spring outlet - Ye Yang; Yao Mu; Xian-Chun Zeng; Weiwei Wu; Jie Yuan; Yichen Liu; E. Guoji; Feng Luo; Xiaoming Chen; Hao Li; Jianing Wang (Ecotoxicology, 2017)